Flipped classroom and psycholinguistic factors : an evaluation - M Alfaifi, Abdullah Ahmad; Saleem, Mohammad (Penerbit Universiti Kebangsaan Malaysia, 2022)
Psycholinguistic factors, i.e., motivation, foreign language anxiety, and self-confidence, affect adult EFL learners’ learning process in a major way, positively or negatively. Research studies show that in a conventional classroom setup psycholinguistic factors affect the learning process of a large number of adult EFL learners negatively because their motivation and self-confidence are low while their foreign language anxiety is high. In the present research study, a survey was conducted with pre-university students in Saudi Arabia who were taught English as a foreign language using Flipped Classroom Model (FCM) as a pedagogy approach. The objective of this investigation was to measure the degree of impact of psycholinguistic factors on the language learning process of students learning English through an unconventional pedagogic approach, that is, Flipped Classroom Model. The results indicate that the teaching approach, even if being highly learner-centred, hardly makes any significant difference to learners’ anxiety, motivation, or self-confidence as regards learning English as a foreign language. However, in comparison to the conventional classroom environment, a slightly less number of learners reported the influence of affective factors on their English learning process under the FCM approach.